Concepções do designer educacional sobre a aprendizagem para o desenvolvimento de recursos multimídia - Araújo, Pedrina Rosa (2011)
This dissertation presents a study about human learning, especially about its new culture, which is used increasingly as a facilitator of technological strategies in online spaces. The aim of this research was limited in the role of educational designer for the learning of students from distance education online courses which was investigated that knowledge these professionals have about learning to develop multimedia educational resources whose intentionality is to help to learning in these spaces. The qualitative research was developed through field study where some interviews were made with selected educational designers as strategy to collect datas. These interviews allowed to emerge from their speeches their conceptions, practices and perceptions about their professional tasks. The studies developed based on the biological and cultural conceptions of learning, conceptions of multimedia learning and cognitive load revealed that these professionals have diverse knowledge about learning, especially in the field of multimedia. However, it was possible to notice that these knowledge are mostly empirical, resulting from their observations and experiences in daily life of their profession which confirmed the premise proposed in this research. As a complex process which involves aspects of diverse natures, the learning is inherent from owner history of mankind, and therefore, it independent on the way that the learning happens, it should always be in focus from all the professionals who involved in the design of educational strategies, among them, the educational designer